2022
DOI: 10.15376/biores.18.1.111-130
|View full text |Cite
|
Sign up to set email alerts
|

Compressive strength of light-weight concrete material made from treated wood waste as a coarse aggregate

Abstract: The effect of replacing the conventional coarse aggregate with wood shavings was evaluated relative to the 28-day compressive strength of the concrete. Six groups were studied: group-1 represented the normal concrete (NC-CTRL1), group-2 (TW-CTRL2) comprised the specimens that had the replacement of the coarse aggregate with raw wood shavings, group-3, group-4, group-5, and group 6 represented the specimens that had the coarse aggregate as coated (treated) wood shavings with cement paste (group-3 and -4) and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In this study, the standard sand was prepared in accordance with the guidelines specified in GB 178-1997 (1979). Aggregates size distribution (Alrubaie et al 2023) is shown in Table 3. The silicon oxide content in standard-sand was greater than 96%, the percentage of the loss of ignition (LOI) was less than 0.4%, and sediment percentage was less than 0.2%.…”
Section: Aggregatesmentioning
confidence: 99%
“…In this study, the standard sand was prepared in accordance with the guidelines specified in GB 178-1997 (1979). Aggregates size distribution (Alrubaie et al 2023) is shown in Table 3. The silicon oxide content in standard-sand was greater than 96%, the percentage of the loss of ignition (LOI) was less than 0.4%, and sediment percentage was less than 0.2%.…”
Section: Aggregatesmentioning
confidence: 99%
“…Hydro-thermal treatment is also used [4,5]. The most promising modification method is wood pressing [6][7][8]. However, this method has a significant drawback: increased formability.…”
Section: Introductionmentioning
confidence: 99%